West from home : letters of Laura Ingalls Wilder to Almanzo Wilder, San Francisco, 1915 - Wilder, Laura Ingalls, 1867-1957 (Harper & Row, 1974)
A selection of letters by Laura Ingalls Wilder to her husband in which she describes the highlights of her visit to the west coast in 1915.